A Juridical Analysis of Post-Pandemic Telemedicine Regulation in Indonesia - I.Wahyudi; K.Yudhoyono (International Medical Journal Corp. Ltd, 2025)
Introduction: The COVID-19 pandemic catalyzed a paradigm shift in healthcare delivery, accelerating the adoption of telemedicine in Indonesia. While temporary ministerial decrees successfully bridged the emergency healthcare gap, the transition into a post-pandemic era requires a permanent, robust juridical framework to ensure legal certainty, patient safety, and physician protection. Methods: This legal research employs a qualitative normative juridical approach, analyzing statutory laws, ministerial regulations, and foundational legal principles governing digital health services in Indonesia. Results: The study reveals that current post-pandemic regulations, primarily under the framework of the new Health Law (UU No. 17/2023) and updated Indonesian Medical Council regulations, still suffer from overlapping jurisdictions, ambiguous standards for cross-border telemedicine, and fragmented liability mechanisms. Discussion: The literature underscores that a cohesive medical-legal architecture is critical. Analysis demonstrates a significant divergence between technical healthcare advancements and current statutory readiness, particularly regarding electronic informed consent, malpractice liability attribution between tech platforms and clinicians, and stringent medical data privacy under the Personal Data Protection Law (UU No. 27/2022). A comprehensive regulatory synthesis is explored to reconcile these operational gaps with statutory doctrines. Conclusions: Indonesia requires an overarching, integrated Government Regulation specifically dedicated to digital health to unify cross-sector obligations. Regulatory authorities must establish clear liability boundaries, standardized digital informed consent protocols, and localized enforcement mechanisms to protect all clinical stakeholders.